2011
DOI: 10.3324/haematol.2011.051995
|View full text |Cite
|
Sign up to set email alerts
|

Comparative clinical effectiveness of prophylactic voriconazole/posaconazole to fluconazole/itraconazole in patients with acute myeloid leukemia/myelodysplastic syndrome undergoing cytotoxic chemotherapy over a 12-year period

Abstract: Post-induction aplasia for acute myeloid leukemia/myelodysplastic syndrome is a high-risk period for invasive fungal diseases. The effectiveness of fluconazole, itraconazole solution, voriconazole and posaconazole prophylaxis used consecutively from December 1998 to January 2010 in patients with acute myeloid leukemia/ myelodysplastic syndrome undergoing remission-induction chemotherapy was retrospectively evaluated. A total of 216 consecutive patients received 573 prophylaxis courses. Breakthrough-invasive fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
105
3
4

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(115 citation statements)
references
References 21 publications
3
105
3
4
Order By: Relevance
“…Despite a pivotal, multi-institutional study (12) and several guidelines (15,17,18), the intensity (i.e., broad-versus narrowspectrum antifungals) and duration of PAP in patients with AML are still a matter of debate (3,13,14). The balance between overtreating patients who might never develop IFI and unfavorable treatment outcomes for patients who develop IFIs because of delays in treatment initiation has tipped in favor of PAP, specifically involving anti-Aspergillus drugs (7,9,10,12,14,15,19). The ideal antifungal for prophylaxis should have potent extended-spectrum activity for both oral and parenteral use and be well tolerated (1,14), with reasonable cost, characteristics not found in a single antifungal drug.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite a pivotal, multi-institutional study (12) and several guidelines (15,17,18), the intensity (i.e., broad-versus narrowspectrum antifungals) and duration of PAP in patients with AML are still a matter of debate (3,13,14). The balance between overtreating patients who might never develop IFI and unfavorable treatment outcomes for patients who develop IFIs because of delays in treatment initiation has tipped in favor of PAP, specifically involving anti-Aspergillus drugs (7,9,10,12,14,15,19). The ideal antifungal for prophylaxis should have potent extended-spectrum activity for both oral and parenteral use and be well tolerated (1,14), with reasonable cost, characteristics not found in a single antifungal drug.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of documented IFIs (definite or probable, according to revised European Organization for Research and Treatment of Cancer [EORTC] criteria) has been reported to range from 12 to 34% in patients with AML (4)(5)(6)(7)(8)(9)(10). In contrast, lower rates of 2 to 6% have been reported for selected patients with AML/myelodysplastic syndrome (MDS) who were enrolled in clinical trials of antifungal prophylaxis (11)(12)(13).…”
mentioning
confidence: 90%
“…Table 1 summarizes the therapeutic strategies adopted. The question regarding the best strategy, stopping fungal prophylaxis [30] or ATRA, is not answered yet. Proposed level III guides for hypercalcemia associated with ATRA in APL are listed below:…”
Section: Hypercalcemiamentioning
confidence: 99%
“…Nevertheless, an Australian observational study by Ananda-Rajah and colleagues comparing fluconazole/itraconazole versus voriconazole/posaconazole prophylaxis in AML/MDS patients supports the main findings of the clinical trial, namely a lower incidence of breakthrough invasive fungal disease (including possible diseases), and less empirical antifungal therapy. 6 In addition, posaconazole prophylaxis also resulted in a lower demand for CT scans, and when a chest CT scan was taken, fewer lesions were seen. However, unselected use of broad-spectrum antifungal prophylaxis also raises concerns about expenditure, overtreatment, toxicity and emergent drug-resistance.…”
mentioning
confidence: 99%